Effect of DTPP-mediated photodynamic therapy on cell morphology, viability, cell cycle, and cytotoxicity in a murine lung adenocarcinoma cell line - Liu, Jianhua; Zheng, Liqing; Li, Yingxin; Zhang, Zhihua; Zhang, Li; Shen, Lixia; Zhang, Xiulong; Qiao, Haixia (Lasers in medical science, 2015)
Photodynamic therapy (PDT) involves the administration and activation of photosensitizing reagents in cancer tissues to induce cytotoxicity. Here we examined the effects of 5-5- (4- N , N -diacetoxylphenyl)-10,15,20- tetraphenylporphyrin (DTPP) -mediated PDT on cell morphology, viability, cell cycle, and cytotoxicity in a murine lung adenocarcinoma cell line. LA795 murine lung adenocarcinoma cell line was used in the study, with cellular uptake of DTPP being quantified by a UV-visible spectrophotometer. The subcellular localization of DTPP was detected by confocal laser scanning microscopy, alteration of cell morphology after PDT was observed by an inverted light microscope, and late-stage apoptosis was examined by terminal dUTP nick end labeling (TUNEL) . The effects of influencing factors on cytotoxicity of PDT in LA795 cells was investigated with varying concentrations of DTPP, energy densities, power densities, and antioxidants by 3- (4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays. Effects of PDT on cell cycle and plasma membrane integrity were studied by flow cytometry analysis. The uptake of DTPP by LA795 cells reached maximum after incubation for 24 h. Confocal laser scanning microscopy showed that DTPP was mainly in the mitochondrion, and slight localization was detected in the lysosomes. Cellular inhibitory effects increased with increased irradiation dose and DTPP concentration, while unactivated DTPP had low toxicity. Flow cytometry analysis revealed that DTPP-PDT-treated cells showed S phase arrest. Cell membrane damage initiation, repair, and irreversible damage were observed at 2, 4, and 5 h after DTPP-PDT , respectively. Together, our results demonstrated cell apoptosis, compromised viability, and cell cycle S phase arrest of LA795 in response to DTPP-PDT , while no effect on the lung cancer cells was observed with irradiation or photosensitizer treatment alone.